Evaporation of Water from Airborne Droplets Containing Sodium Chloride, Mucin, and Surfactant - Keita Kurai; Hikaru Miyamoto; Nobuyuki Takegawa (Aerosol and Air Quality Research)
Abstract We conducted laboratory experiments to investigate the evaporation of water from airborne model respiratory droplets containing sodium chloride (NaCl) as an inorganic salt, mucin as a glycoprotein, and dipalmitoylphosphatidylcholine (DPPC) as a surfactant. The model respiratory droplets were introduced into a flow tube, in which the relative humidity (RH) was controlled at 30%, 50%, and 70%. The residence time of the model droplets under the RH-controlled conditions was altered by varying the length of the flow tube. Size-segregated particle number concentrations were measured using an optical particle counter placed at the end of the flow tube vented to the atmosphere. The particle number size distributions for NaCl exhibited systematic changes with an increasing RH. The particle number size distributions for (NaCl + mucin) and (NaCl + mucin + DPPC) exhibited very weak RH dependency. These results suggest that the presence of mucin and DPPC had a significant effect on the RH dependency of the evaporation of water from the model droplets.